Prestise di Balik Perayaan Kematian: Kajian Budaya Atas Film Tulang Belulang Tulang - Naila Abyantika Pramesthi; Else Liliani (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study identifies the cultural dynamics present in the film Tulang Belulang Tulang (2024) by Sammaria Sari Simanjuntak using Raymond Williams’ theory, specifically focusing on dominant, residual, and emergent values. This study employs a qualitative approach using content analysis. Data were collected by observing and recording dialogues and visual elements that illustrate cultural dynamics in the film Tulang Belulang Tulang. The data analysis technique used is the Miles and Huberman method, which consists of data reduction, data presentation, and drawing conclusions. This study identified 15 data points comprising cultural dynamics according to Williams, namely dominant, residual, and emergent. The results reveal three layers of culture within the Mangokal Holi traditional ceremony. Seven data points represent dominant culture. Dominant culture exerts hegemony over traditional practitioners in terms of social status. Meanwhile, three data points were identified under residual values. Residual values seek to preserve the sanctity of ancestors amidst modernity. Furthermore, four data points represent emergent values. The presence of emergent values serves as a critical form that prioritizes rationality and honesty. These three value categories demonstrate that culture is a dynamic interplay between the legacy of the past, the demands of the present, and the ethical corrections of the future. This study makes a theoretical contribution by expanding the application of Raymond Williams’s cultural theory to Indonesian films, while also enriching critical scholarship on the dynamics of local cultural adaptation in the modern era. Keywords: cultural studies, Raymond Williams, Batak culture, Mangokal Holi, Tulang Belulang Tulang.